HAMBATAN KOMUNIKASI ORGANISASI MAHASISWA SELAMA MASA PEMBELAJARAN JARAK JAUH PADA PERGURUAN TINGGI DI JAKARTA - Windhiadi Yoga Sembada; Adella Melinda; Irpan Ripa’I Sutowo (Jurnal Pustaka Komunikasi, 2022)
The Covid-19 pandemic has forced all lecture activities to be carried out online, including organizational activities. This has hampered many organizations in carrying out their work programs. This research was conducted to determine the obstacles that occur in organizational communication at HIMAIKOM FISIP UPN Veteran Jakarta during the Distance Learning period using Wursanto's concept of organizational communication barriers, namely; technical barriers, semantic barriers, behavioral barriers, structural barriers, distance barriers, and background barriers. The research method used is qualitative with a case study approach and uses primary and secondary data sources. The data collection technique was carried out by Focus Group Discussion (FGD) in which the informants were selected by purposive sampling technique. The data obtained were then analyzed through four stages of data analysis, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the six organizational communication barriers in HIMAIKOM are found according to the types of organizational communication barriers according to Wursanto. In addition, there are two new findings which are also factors that hinder organizational communication, namely gender differences and closeness between members.